Endurance Training for Volleyball Athletes: The Efficacy of Tabata and Circuit Training Models - Ervan Kastrena; Rinda Mega Revianny (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Volleyball matches can be very long, especially if the two teams are evenly matched. Physical endurance is essential to maintain high performance during matches that may last up to five sets. Athletes who have good endurance can continue to move, jump, and perform fast movements throughout the game without experiencing excessive fatigue. Tabata training and circuit training are two types of training that focus on improving physical fitness with different methods, such as training duration and training format. The aim of this study was to examine the effect of tabata training and circuit training on increasing the endurance of volleyball athletes. In this research, researchers applied an experimental method with a pre-test post-test control group design. The research samples consisted of 30 athletes from the Tectona club in Cianjur Regency. The instrument for measuring the endurance of volleyball athletes was the yoyo test. Samples were receiving treatments 3 times a week with a total of 18 meetings. Hypothesis testing used paired sample-test and independent sample-test analysis. The research results showed that both tabata training and circuit training had an effective influence in increasing endurance of volleyball athletes, but the circuit training showed a more effective result compared to the tabata training. The study concludes that both of the training models have positive effects on increasing endurance of volleyball athletes, but the circuit training model has a more effective influence on increasing endurance.